Resilience of family caregivers of children and adolescents in treatment of neoplasms and associated factors. - Scalabrin da Silva, Jaqueline; Fereira Moraes, Otavio; Dressler Sabin, Luiza; Ormizinda Almeida, Franciele; Bosi de Souza Magnago, Tânia Solange (Revista Brasileira de Enfermagem, 2021)
Objectives: analyze the level of resilience of family caregivers of children and adolescents hospitalized for cancer treatment and associated factors. Methods: cross-sectional study, carried out in 2018, with 62 family caregivers in a university hospital in the state of Rio Grande do Sul, Brazil. The instruments CDRisc-10-Br, SRQ20, PSS-14 and WHOQOL-Bref were used to measure resilience, minor psychological disorders, stress, and quality of life, respectively. Inferential statistics were used. Results: female caregivers, married, with one child and who practice some predominated religion. They were classified as having a moderate level of resilience (48.4%); with suspicion for minor psychological disorders (45%) and high level of stress (41%). In terms of quality of life, they were satisfied in the Physical, Psychological and Social Relations domains; and dissatisfied in the Environment domain. Conclusions: there were direct weak to moderate correlations between the level of resilience and quality of life and inversely with stress and minor psychological disorders.